Exact Periodic Wave, Bisoliton, and Various Breather Solutions for the Zakharov Equations. (8th December 2015) - Wang, Heng; Chen, Longwei; Liu, Hongjiang; Zheng, Shuhua
Abstract : The Zakharov equations, which involve the interactions between Langmuir and ion acoustic waves in plasma, are analytically studied. By using the method of Exp-function, the periodic wave, bisoliton, Akhmediev breather, Ma breather, and Peregrine breather of the Zakharov equations are obtained. These results presented in this paper enrich the diversity of solution structures of the Zakharov equations. Furthermore, based on the numerical simulations of these solutions, some physics analysis of bisolitons and various breathers are given.